The effect of reverse roleplay training to improve the counselor’s mind skills - Lutfi Fauzan; Nur Hidayah; Fitri Wahyuni; Husni Hanafi; Rofiqoh Rofiqoh; Nanda Alfan Kurniawan (Intelektual Pustaka Media Utama, 2023)
Mind skills become the counselor’s internal competencies that support the counselor’s self-development in providing guidance and counseling services. Mind skills consist of six components that are interrelated and often integrated. The metacognitive thinking process is the key to success in how counselors can manage their thoughts and mental states through these six components. This study examined the success of the reverse roleplay training strategy to improve the counselor’s mind skills. The method was quasi-experimental quantitative with a pretest-posttest design. The subjects of this study were 31 counselors in Malang Raya, Indonesia. Data analysis in this study used two stages, descriptive statistical analysis and hypothesis test. The results showed that the counselor’s mind skills achievements before and after the intervention marked a difference with significant increase. Reverse roleplay increased the participants’ understanding and experience of the thoughts, perceptions, and feelings from broader perspectives. The counselor’s mental experiences involved during counseling sessions become a “full presence” for the therapeutic relationship. This research suggests further research to explore the counselor’s mental experiences in detail. As for practical implication, the reverse roleplay is recommended as a training design for improving the internal competencies of counselors and educators in general.